2003
DOI: 10.1364/ao.42.004612
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spatially and temporally resolved diffuse-reflectance measurement systems for determination of biomedical optical properties

Abstract: Time-resolved and spatially resolved measurements of the diffuse reflectance from biological tissue are two well-established techniques for extracting the reduced scattering and absorption coefficients. We have performed a comparison study of the performance of a spatially resolved and a time-resolved instrument at wavelengths 660 and 785 nm and also of an integrating-sphere setup at 550 -800 nm. The first system records the diffuse reflectance from a diode laser by means of a fiber bundle probe in contact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 30 publications
1
76
0
Order By: Relevance
“…Since imaging depths generally do not exceed ≈ 1 mm, this may well be justified for weakly scattering media (µ t < 6 mm -1 for the samples used in this paper). We first compare the single scattering model [4,5,6] to a multiple scattering model [7] using the same calibrated scattering samples with µ t ranging from 2 mm -1 to 6 mm -1 described in [15] and used in a similar analysis in [8]. The experiments are performed under the condition of dynamic focusing (i.e., the focal plane coincides with the probing location) such that the influence of the confocal properties during the depth scan is constant.…”
Section: Choosing a Model For The Oct Signalmentioning
confidence: 99%
“…Since imaging depths generally do not exceed ≈ 1 mm, this may well be justified for weakly scattering media (µ t < 6 mm -1 for the samples used in this paper). We first compare the single scattering model [4,5,6] to a multiple scattering model [7] using the same calibrated scattering samples with µ t ranging from 2 mm -1 to 6 mm -1 described in [15] and used in a similar analysis in [8]. The experiments are performed under the condition of dynamic focusing (i.e., the focal plane coincides with the probing location) such that the influence of the confocal properties during the depth scan is constant.…”
Section: Choosing a Model For The Oct Signalmentioning
confidence: 99%
“…For these experiments, we used six phantoms from a previous investigation [19] with three distinct values of µ s and two distinct values of absorption coefficient µ a , respectively. The phantoms consisted of epoxy resin (n=1.55) with well-defined quantities of scattering material and absorbing pigment added for scattering and absorption purposes, respectively.…”
Section: Phantomsmentioning
confidence: 99%
“…In all phantoms used, it was ensured that absorption effects were negligible compared to those from scattering. Mounting the phantoms in a slab geometry was achieved by sandwiching 1 ml of each phantom between two microscope slides before the epoxy hardened yielding 1.0 mm thick samples with a cross section measuring 3 x 3 cm 2 [19].…”
Section: Phantomsmentioning
confidence: 99%
“…21 Most of the in vivo studies mentioned above have relied on a simple head model described as a homogeneous semi-infinite medium. 1,[6][7][8][9][10]16,[19][20][21][22]25,26 This model has shown promising results in piglets and infants, 5,8,9,11,20,22,27 but it is widely recognized that, in the case of the adult head, its oversimplification causes strong contamination of the brain optical properties by those of the extracerebral tissue. For the FDMD approach, Franceschini et al 12 have shown, with simulations and phantom measurements in a slab geometry, that when a superficial layer thicker than ∼1 cm is present, the error on the retrieved absorption of the second layer can exceed 50%.…”
Section: Introductionmentioning
confidence: 99%